2012
DOI: 10.1007/s11947-012-0813-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Starches on Rheological Properties of Ketchup

Abstract: The aim of this work was to study the effect of commercial modified starches of different origin on rheological properties of ketchup. The following starches were used to produce the ketchup samples: chemically modified potato (acetylated distarch adipate from potato starch), waxy maize (acetylated distarch adipate from waxy maize starch and hydroxypropyl distarch phosphate from waxy maize starch), and cassava (acetylated distarch adipate from cassava starch) starches and physically modified cassava and waxy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 25 publications
5
45
0
6
Order By: Relevance
“…On the other hand, the distribution of the particle size of the other two preparations, pre-gelatinised acetylated distarch adipate (product 12616) and pre-gelatinised hydroxypropyl distarch phosphate (product 12650) significantly deviated from normal, which was reflected in a large span and a relatively large standard deviation from the mean diameter of a particle. A similar size distribution of modified waxy starches was observed by Bayod et al (2008) and Juszczak et al (2013).…”
Section: Resultssupporting
confidence: 82%
“…On the other hand, the distribution of the particle size of the other two preparations, pre-gelatinised acetylated distarch adipate (product 12616) and pre-gelatinised hydroxypropyl distarch phosphate (product 12650) significantly deviated from normal, which was reflected in a large span and a relatively large standard deviation from the mean diameter of a particle. A similar size distribution of modified waxy starches was observed by Bayod et al (2008) and Juszczak et al (2013).…”
Section: Resultssupporting
confidence: 82%
“…It is likely that the larger peak (10 µm) is associated with the oil droplets stabilized by a layer of egg yolk proteins in normal mayonnaise (Muller et al, 1998;Worrasinchai et al, 2006;Rayner et al, 2012), and the smaller peak (70 µm) is associated with the modified potato starch which is used as a thickening agent. Juszczak et al (2013) reported the particle size of granules of acetylated distarch adipate (ADA) corn and potato starches in ketchup suspension is in the range of 50-100 µm. Whereas, in the sample with 75% egg yolk replacement (curve b), the main peak at 10 µm is much smaller than that of the control because the oil droplets are mainly surrounded by DSA starch instead of egg yolk, and in the sample with 100% replacement (curve c), this peak seems to be completely vanished.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they are the most suited starches for use in fruit pie fillings, ketchup, and sauces 2, 4. Therefore, they are the most suited starches for use in fruit pie fillings, ketchup, mayonnaise, sweet and sour sauces, and baked, frozen, and canned foods 2, 4, 5, 6. In some European Union countries, particularly in Poland, potatoes are one of the major raw materials for the production of starch, hence potato starch derivatives are readily available and widely used 7.…”
Section: Introductionmentioning
confidence: 99%
“…fruits, can play an important role both in creation and stabilization of texture, and the perception of flavor in such products as fruit fillings and sauces, fruits in gel, or ketchup. Therefore, selection of appropriate modified starch is a key factor influencing consumer acceptance of the composed products 5, 31, 32.…”
Section: Introductionmentioning
confidence: 99%